Functionalized Multi-Walled Carbon Nanotubes as Heterogeneous Lewis Acid Catalysts in the Etherification Reaction of tert-Butyl Alcohol and Ethanol. Issue 10 (2nd October 2016) - Yee, Kian Fei; Ng, Eng-Poh; Mohamed, Abdul Rahman; Adam, Farook; Tan, Soon Huat
Abstract : Most of the conventional catalysts exhibited limitations in catalyzing etherification reactions. In this study, functionalized multi-walled carbon nanotube (F-CNT) catalyst containing Lewis acid sites were prepared via functionalization with sulfuric acid and the catalytic performances in the etherification of tert -butyl alcohol (TBA) with ethanol were investigated. Characterization of F-CNTs with thermogravimetric analysis, Raman spectroscopy, Fourier transform-infrared spectroscopy, pyridine adsorption, temperature-programmed desorption of ammonia and nitrogen adsorption were performed to correlate the characteristics with the catalytic performances. The catalyst showed a high catalytic performance and high selectivity in the etherification reaction. The best reaction conditions obtained consist of 4 h of reaction time at 140°C, an ethanol:TBA molar ratio of 2:1 and a catalyst loading of 3 wt%. The best conversion of TBA and TBA selectivity toward ethyl tert -butyl ether (ETBE) were 64% and 68%, respectively. No significant degradation of the catalytic performance was observed after four consecutive reactions and the catalyst was easily regained after regeneration. A mechanism for the etherification reaction was also proposed.